Investigation of validity evidence for the Coach Precompetitive Communication Questionnaire-Preference for measurement of collegiate athlete preferences of coach speech content and delivery - Zimmerman, Corinne T.; Myers, Nicholas D.; Vealey, Robin S. (Frontiers in Sports and Active Living, 2025)
IntroductionPrevious measures of athlete perception of pregame speech have centered around a two-dimensional structure of speech content (i.e., tactical and emotional), although psychometric evidence is limited. The Coach Precompetitive Communication Questionnaire – Preference (CPCQ-P) was developed to extend the two-dimensional model of pregame speech content by (a) including speech delivery and (b) allowing a general pregame speech factor. The purpose of this study was to investigate initial validity evidence for responses to the CPCQ-P under an exploratory bifactor approach at the athlete level.MethodsParticipants were athletes (N = 264) at level-1 nested within NCAA varsity level teams (G = 36) at level-2. Participant survey responses were analyzed using an exploratory bifactor analysis with a general factor (i.e., pregame speech) and three grouping factors (i.e., tactical content, emotional content, delivery).ResultsA four-factor model with three grouping factors and a general factor exhibited approximate to close fit to the data. Review of factor loadings provided initial evidence of validity for the internal structure of responses to the CPCQ-P.DiscussionThis study expands the existing psychometric understanding of pregame speech within the collegiate sport context.